KINERJA KOPERASI DI INDONESIA - Abi Pratiwa Siregar (JURNAL VIGOR, 2020)
This research aims to determine the performance of co-operatives in Indonesia in terms of financial and non-financial aspects. The basic method of this research is analytical descriptive using secondary data from publications of the Ministry of Co-operatives and SMEs. Initially, data from 2000 to 2019 will be used, but from 2016 to 2019, the data is temporary so it cannot be compared with previous years which are fixed data. Financial performance is measured using DER, NPM, and ROE. Meanwhile, financial performance is known by various parameters, namely the number of active co-operatives, the number of inactive co-operatives, the proportion of inactive co-operatives to the number of co-operatives, the development of the number of members, the proportion of co-operatives conducting annual member meetings (RATs) to the number of active co-operatives, and the development of the number of managers ( managers and employees). The results showed that the financial performance of co-operatives in Indonesia showed positive developments or getting better. However, the capital structure of co-operatives over time is increasingly dominated by external capital which is generally in the form of debt. In the non-financial aspect, co-operatives in Indonesia show a declining development: The number of inactive co-operatives is increasing as the number of co-operatives increases, active co-operatives but not implementing RATs show an increasing tendency, the number of members decreases and labor absorption has not been able to be maximized due to limitations co-operatives both financially and organization readiness.